Forged in flames eaudiobook - Smoak, Ivy (Made of Steel, 2019)
It's hard to be consumed by revenge when my heart feels like it's breaking in two. A part of me is still in love with Miles. I think I always will be. He embodies everything I thought my life could be. Every hope and dream and wish. But I'm not the girl that he remembers. And I'd be lying if I said I haven't started to fall for the New York City vigilante. He's the only other person that knows what it's like to live behind a mask. There's a darkness in him that mirrors my own. He embraces my broken soul. But I'm tired of all the secrets, masks, and lies. I don't need a man to save me. I'm the superhero of my own story. And all I need to focus on right now is Don Roberts—a monster far worse than I ever imagined—before he unleashes the mafia on this city and ruins any chance I have at a new life.